Reducing premature mortality from cardiovascular diseases in low and middle income countries: The role of Polypill in public health policy - Sadaf G. Sepanlou; SeyedehFatemeh Mousavi; Hossein Poustchi; Fatemeh Malekzadeh; Gholamreza Roshandel; Reza Malekzadeh (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Premature deaths account for about half of all fatalities in developing countries. In low- and middle-income countries, cardiovascular diseases have consistently been the primary cause of premature mortality for men and women during the past three decades.Current evidence indicates that fixed-dose combination therapy, the so-called Polypill, effectively reduces the burden of cardiovascular diseases, with greater benefits observed in combinations that include aspirin. Polypill demonstrates high adherence and an acceptable safety profile, with adverse drug events being comparable between the groups receiving treatment and those in the control group.Therefore, this paper advocates for the broader implementation of Polypill in low and middle-income countries, emphasizing its efficacy in the primary and secondary prevention of cardiovascular diseases. The strategy could also benefit high-risk groups with special conditions, such as non-alcoholic fatty liver disease and chronic kidney disease. The cost-effectiveness of Polypill and its potential to address health inequities in low and middle-income countries underscore its value as a public health strategy. Policymakers are encouraged to consider Polypill as a viable option to enhance cardiovascular health outcomes and reduce premature deaths in low-resource settings.